Student perception regarding the utilization of media literacy to prevent online threats, Thailand - Thairoongrojana, Smitthinun; Ruangsan, Niraj (Linguistics and Culture Review, 2021)
The objective of this research was to study students’ perception of using media literacy (ML) to prevent online threats of the students majoring in Communication Arts, Faculty of Management Science, Suan Sunandha Rajabhat University (SSRU). Selected by Purposive Sampling, the samples (n = 60) of this research were the students majoring in Communication Arts, Faculty of Management Science, SSRU. The research tool was the student perception questionnaire with 4 sections: 1) personal data, 2) perception on ML (60 questions), 3) benefits of ML for students (10 questions), 4) implementation of ML (11 questions), and (5) open-ended questions (2 questions). The finding suggested that most students have paid attention to awareness on using OSM with carefulness as effects from posting messages, images, or video clips on oneself, others, and family members. The most agreed benefit of ML is that students can develop values, morality, and ethics as a result of their ML education. The application of ML in their life is based on their ML skills.